2010
DOI: 10.1111/j.1439-0485.2009.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐sea demersal fish species richness in the Porcupine Seabight, NE Atlantic Ocean: global and regional patterns

Abstract: The ichthyofauna of ocean margin regions is characterised by a succession of different species occurring at different depths. This study was aimed at determining whether the resultant pattern of species richness with depth is a consequence of local factors in a given region or whether it simply reflects the global pattern of fish species distribution in the oceans. Along the ocean margin of the temperate NE Atlantic Ocean in the Porcupine Seabight and Abyssal Plain region, 48°-53°N, a total of 108 demersal fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 52 publications
(82 reference statements)
3
45
1
Order By: Relevance
“…n max : peak abundance; %frames: percentage of frames in which at least 1 individual was observed; t 0 : time of first arrival; na: not applicable suggests an increasing importance of carrion in the diets of demersal fishes and a shift to an opportunistic foraging strategy at deeper portions of continental margins. This finding contrasts with observations in the NE Atlantic where Priede et al (2010) found scavenging fish to comprise a constant proportion of the fish fauna (22.7%) from 240 to 4965 m. This result was an average across depths. If the data presented in Fig.…”
Section: Scavenging Behavior and Depthcontrasting
confidence: 99%
See 1 more Smart Citation
“…n max : peak abundance; %frames: percentage of frames in which at least 1 individual was observed; t 0 : time of first arrival; na: not applicable suggests an increasing importance of carrion in the diets of demersal fishes and a shift to an opportunistic foraging strategy at deeper portions of continental margins. This finding contrasts with observations in the NE Atlantic where Priede et al (2010) found scavenging fish to comprise a constant proportion of the fish fauna (22.7%) from 240 to 4965 m. This result was an average across depths. If the data presented in Fig.…”
Section: Scavenging Behavior and Depthcontrasting
confidence: 99%
“…If the data presented in Fig. 4 are averaged, the resulting value of 22% would be very close to that presented by Priede et al (2010). It is interesting to note that at depths <1000 m, the data in Priede et al (2010) yield percentages of <10%, similar to our own findings.…”
Section: Scavenging Behavior and Depthsupporting
confidence: 84%
“…Although the fit and model predictions computed for GAMM_depth_lat-also those based on a cross-validation procedure-are superior over the other models under study, the resulting distribution of roundnose grenadier as a function of depth is bimodal, with the first (lower) modal value around 1,000 m and the second (upper) mode at 1,600 m of depth. The bimodal distribution of roundnose grenadier is biologically improbable (PRIEDE et al 2010;REX and ETTER 2010), and a potential explanation should be sought in the relatively limited number of data points available in each period. Indeed, the sparse data points are spatially clustered and thus it is difficult to unequivocally confirm the bimodal pattern of the distribution curve.…”
Section: Discussionmentioning
confidence: 99%
“…50°N, 13°W) were surveyed by scientific bottom trawl from 1977 to 2002. For the present analysis we used trawls at depths ranging from 800 to 4,865 m [=146 trawls, GODBOLD et al (2013)], which is a subset of the full data described by BAILEY et al (2009) andPRIEDE et al (2010). Trawls from depths \800 m were excluded from the analysis as no shallow water trawling was carried out after 1989.…”
Section: Trawling Datamentioning
confidence: 99%
See 1 more Smart Citation